Compósito de poliéster e fibra de vidro na confecção de hastes intramedulares bloqueadas para osteossíntese de fraturas femorais em bovinos - Sergio da Silva Rocha Junior (2019)
The objective was to test a composite of polyester resin and fiberglass in the form of an intramedullary nail for osteosynthesis of femoral fractures in calves. The methodology was established based on a previous study, which used finite elements model to simulate a femoral fracture stabilized by the proposed nail. In a first experiment, the composite biocompatibility was assessed after insertion of a composite fragment into the subcutaneous tissue of seven Wistar rats. In the second experiment, the composite was evaluated in cattle as an intramedullary nail. General anesthesia was induced in six calves, the fracture was induced by oblique incision in the middle third of the diaphysis, and the femur was immediately stabilized by the retrograde insertion of the nail. The blocking occurred by the transversal application of four stainless steel screws, two applied proximal and two distal to the fracture line. In the first experiment, the composite considered acceptable as mild irritant. In the second, five of the six calves obtained complete consolidation of the fracture after 60 days. No signs of incompatibility or toxicity of the composite were observed. However, some limitations were reported during surgery, such as difficulty in drilling the nail and the removal of the leftover material that exceeded the medullar canal. Small fragments produced by these maneuvers were considered irritant for tissues and were associated with the occurrence of seromas in the post-operative period. It was also found that small fractures in the nail tended to propagate in the form of longitudinal ones. In conclusion, the intramedullary nail of polyester resin and fiberglass (a low cost and easy to acquire material) was considered biocompatible and able to permit femoral fractures consolidation in young cattle. However, further development of solutions to the reported limitations are needed before its clinical recommendation.